An Introduction to Spatial Data Analysis : Remote Sensing and GIS with Open Source Software /: Remote Sensing and GIS with Open Source Software. (2020) - Wegmann, Martin; Schwalb-Willmann, Jakob; Dech, Stefan
No abstract available